Professional Relationship Development Through Nursing Care Delivery System Training in Nursing Education - Aria Pranatha; Abdal Rohim; Khusnul Aini; Ranto Karyanto (International Journal of Educational Narratives, 2026)
Background. However, a significant "theory-practice gap" persists, where nursing students often struggle to apply relational skills in complex clinical environments, potentially leading to medical errors and suboptimal care. Purpose. This study aims to evaluate the effectiveness of Nursing Care Delivery System (NCDS) training in enhancing these professional relationships among nursing students. Method. A quantitative approach with a quasi-experimental one-group pretest-posttest design was conducted on 60 nursing students selected via total sampling. Results. The findings revealed a statistically significant improvement in relational scores (t = -7.010, p = 0.000) with an average increase of 19.63% (N-Gain = 0.1964). Despite this positive shift, the results suggest that the training’s impact was not yet uniform across all participants. Conclusion. This study’s novelty lies in transforming the NCDS model from a technical task management tool into a holistic relational framework that integrates social dynamics and clinical roles.